The relationship between school bullying victimization and social mindfulness in middle school students: a chain mediating model of self-concept clarity and cognition reappraisal - Yang, Weijing; Hu, Dong; Guo, Ying (Frontiers in Psychology, 2024)
Objective To determine the relationship between school bullying victimization and social mindfulness and its mechanism in light of the interdependence and schema theories. Method The Chinese version of the Delaware Bullying Victimization Scale-student, Emotion Regulation Questionnaire, Self-Concept Clarity Scale and The Social Mindfulness Self-report Scale (SMSRS) were distributed to 553 middle school students. Results (1) The correlations of school bullying victimization with social mindfulness, self-concept clarity, and cognition reappraisal were statistically significant. (2) School bullying victimization had a significant effect on social mindfulness. (3) The simple mediating role of self-concept clarity and cognition reappraisal between school bullying victimization and social mindfulness were significant. (4) Self-concept clarity and cognition reappraisal played a chain mediating role between school bullying victimization and social mindfulness.